Critical evaluation of seven lactation curve estimation models - Marek Jaroslav; Rajmon Radko; Haloun Tomáš (Springer, 2015)
A mathematical model of the lactation curve approximation provides summary information about dairy cattle production, which is useful in making management and breeding decisions and in simulating a dairy enterprise. Several nonlinear regression models have been devel- oped during the past decades. Unfortunately, there is no unique algorithm in literature. The question of choosing the best function is brought up. We tested seven such models (Gaines, Nelder, Ning-Yang, Marek-Zelinkova, McMillan, Papajesic-Bodero, Wood) using milk yield data of more than 5 000 lactation cycles. Non-linear approximations showed high level of confidence in all models. Critical limitations of individual approaches are discussed using data of several individual cows with problematic approximations. We stress the limitations of individual generally well-fitting mathematical models at the level of individual animals. The best results were obtained with Wood, Nelder or Marek-Zelinkova models.
Kritické zhodnocení sedmi modelů pro odhad laktační křivky
Keywords: 305-day yield estimate, fitting of lactation curve, approximation of nonlinear function, nonlinear regression.; odhad 305-denního nádoje, aproximace laktační křivky, aproximace nelineární funkce, nelineární regrese